PRAKTIK BLACK MARKET PADA KASUS PENJUALAN IPHONE SECOND DI INDONESIA TAHUN 2016–2020 - Adelia Ananda Salsabila; Maria Indira Aryani (Journal Publicuho, 2022)
The iPhone is a smartphone designed and marketed by Apple Inc. with a distinctive brand image. It has technological advantages that cause the iPhone to have an expensive market price. The iPhone's high price in Indonesia has led to the spread of black-market iPhones that come from black market imports and sold after a reconditioning process. Those black-market iPhones followed by unofficial repairs and without an official warranty. This research aims to discover the cause of the high sales figures of black-market iPhones in Indonesia. This research is analyzed using the theory of black-market prices and the black-market concept: supply and demand effects of legalization. This research is qualitative explanatory, which aims to see the cause and effect of the phenomena. The research showed that the high demand of the black-market iPhones in Indonesia is due to the affordable prices, different tax levels, and the forming regulation of IMEI (International Mobile Equipment Identity) validity to respond to the sales/entry of the black-market iphone in Indonesia and the existence of IMEI registration policy for imported iPhones.